Personal Brand: concept and evolution. The influence of the press in the creation of a personal brand in the Victorian era - de la Morena Taboada, Marián (Historia y Comunicación Social, 2014)
The nineteenth century is one of the most prolific periods in the history of the anglo-saxon literature. It is also a moment of rapid expansion for the press and the connection between literature and journalism is enhanced by the publication of an abundant number of short stories in the most important newspapers. These stories are written by a group of writers evolving from a literary tradition which can be traced back to the first colonies established in the eastern coast of the U.S.A whose population came mainly from Britain and Ireland. Short stories are deeply rooted in the American literature and closely related with the press where they found the perfect vehicle for its transmission. Henry James is a good example of this tradition that he combined with the writing of thick volumes. Authors were known through the press and they could reach a much wider audience who could found good literature inside the newspapers they bought. So the concept of personal brand is not a new one created by marketing strategies (Pérez Ortega, 2012). It is simply a way to identify an image, a symbol or a person as something valuable, reliable and desirable.